2020
DOI: 10.1016/j.foodchem.2019.125530
|View full text |Cite
|
Sign up to set email alerts
|

A label-free ultrasensitive microfluidic surface Plasmon resonance biosensor for Aflatoxin B1 detection using nanoparticles integrated gold chip

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Bhardwaj et al developed a SPR-based biosensor using antibodies to detect AFB1. The surface immobilization of anti-AFB1 antibodies by coating with AuNPs amplified the signal and reduced the LOD to 0.003 nM [ 120 ]. Othman and Wollenberger achieved an amperometric biosensor using immobilized laccase as the sensing element in the detection of phenolic NPs.…”
Section: Emerging Biosensor-based Detection Methods Of Natural Producmentioning
confidence: 99%
“…Bhardwaj et al developed a SPR-based biosensor using antibodies to detect AFB1. The surface immobilization of anti-AFB1 antibodies by coating with AuNPs amplified the signal and reduced the LOD to 0.003 nM [ 120 ]. Othman and Wollenberger achieved an amperometric biosensor using immobilized laccase as the sensing element in the detection of phenolic NPs.…”
Section: Emerging Biosensor-based Detection Methods Of Natural Producmentioning
confidence: 99%
“…However, the liquid sample volumes and power consumption of a SPR-based biosensor are still bulky, and the sensitivity and resolution of those SPR-based biosensors or devices need to be further improved, which have been the main bottlenecks in the fabrication of SPR-based biosensors for biomedical applications. To circumvent these drawbacks, nanomaterials, microfluidic devices, and compact as well as power-free pump systems have been attempted to integrate SPR-based biosensor systems [230] , [241] , [242] , [243] , [244] , [245] , [246] , [247] . In one example, an innovative SPR-based biosensor was developed for highly sensitive detection of HIV-related DNA based on entropy-driven strand displacement reactions and double-layer DNA tetrahedrons for SPR signal enhancement ( Fig.…”
Section: Detection Methods For Poc Diagnostic Applicationsmentioning
confidence: 99%
“…SPR sensors have also been used in diverse healthcare biosensing applications, bioimaging paediatric burns [75] as well as in the study of mutations [76] and the effects of radiation exposure [77]. Recent studies have also shown the versatility of such devices in the study of pathogens [78], thermal injuries [79], carcinogens [80] and several clinically vital molecules [81][82][83].…”
Section: Surface Plasmon Resonance Sensors For Biomedical Diagnosticsmentioning
confidence: 99%